Simulation based optimization of aeration in carousel reactors for securing new EU discharge regulations - Özdemir, Irmak (Graduate School, 2024)
This study provides a comprehensive evaluation of the Wastewater Treatment Plant (WWTP) in the Black Sea Region using advanced process simulation tools. The primary goal is to analyze both the design and operational efficiency of the plant, ensuring that it operates within optimal parameters and meets stringent regulatory standards. Key metrics such as effluent quality, sludge production, and oxygen demands were systematically assessed against the plant's design documents and simulation results. The plant encompasses several treatment units, including a sand-grease chamber, Bio-P reactors, Carousel reactors, final clarifiers, and a disk filtration unit. Additionally, the sludge management system employs mechanical thickeners and dewatering facilities, optimizing the handling and processing of sludge to enhance overall treatment efficiency and sustainability. The simulations focused on the coordinated operation of three Bio-P reactors, three Carousel tanks, and three final clarifiers, highlighting their role in enhancing treatment efficiency and ensuring compliance with regulatory standards for effluent quality. This study conducts a simulation of the WWTP, evaluating its design against performance metrics such as effluent quality, sludge production, and airflow rate. The results confirmed compliance with discharge limits for Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Total Nitrogen (TN), and Total Phosphorus (TP), thereby validating the plant's operational efficacy using real wastewater data. The dissolved oxygen set-point, critical for maintaining optimal biological activity, is regulated through simulation, specifically for the short carousel reactor utilized in the design. This approach ensures that the biological processes involved in nutrient removal are functioning efficiently, thereby enhancing the overall performance of the treatment plant. In carousel tanks with a low aspect ratio, dissolved oxygen (DO) levels play a critical role in the removal of nitrogen and phosphorus. These tanks are commonly used in biological nutrient removal (BNR) systems and optimizing aeration processes enhances the efficiency of nitrogen and phosphorus removal. Nitrogen removal relies on nitrification and denitrification processes. During nitrification, ammonium is oxidized to nitrite and then to nitrate, requiring high DO levels; low DO levels can reduce the nitrification rate, leading to ammonium accumulation. In the denitrification process, nitrate is reduced to nitrogen gas under anoxic (oxygen-free) conditions. Proper management of DO levels ensures the efficient execution of nitrification and denitrification processes, allowing simultaneous nitrification and denitrification (Simultaneous Nitrification-Denitrification, SND) to occur in the same tank. This reduces operational costs while enhancing nitrogen removal efficiency. Phosphorus removal depends on the activity of polyphosphate-accumulating organisms (PAOs). PAOs release phosphate under anaerobic conditions and take it up again under aerobic conditions. Proper management of DO levels ensures this cycle operates efficiently. Additionally, in simultaneous denitrifying phosphorus removal processes, nitrate is used as an electron acceptor, and low DO levels create the anoxic conditions necessary to enhance phosphorus removal efficiency. Therefore, optimizing DO levels in low aspect ratio carousel reactors enhances biological processes and reduces energy consumption. Proper placement and adjustment of aeration equipment ensure DO levels are maintained within the desired ranges. Dynamic DO control systems, which monitor biological activity in real-time and automatically adjust DO levels based on this activity, further improve nitrogen and phosphorus removal efficiency. Management of DO levels in low aspect ratio carousel tanks significantly improves nitrogen and phosphorus removal. This not only ensures compliance with environmental regulations but also increases energy efficiency, reduces operational costs, and contributes to sustainable wastewater management practices. These findings provide critical insights into the plant's operational strengths and areas for improvement. They serve as essential guidance for the appropriate dimensioning of bioreactors and the optimization of operational parameters, ensuring adherence to new EU discharge directives. The study not only confirms the plant's capability to meet stringent effluent quality standards but also underscores the importance of advanced simulation tools in achieving sustainable wastewater management. By leveraging these tools, the research highlights how simulation can be used to predict plant performance under various conditions, identify potential bottlenecks, and develop strategies to mitigate these issues before they impact the plant's operations. Furthermore, the study emphasizes the role of simulation in optimizing energy consumption within the WWTP. By accurately modeling the oxygen demands of the biological processes, the study provides recommendations for fine-tuning the aeration systems, which are among the most energy-intensive components of the treatment process. This not only helps in reducing operational costs but also contributes to the environmental sustainability of the plant by lowering its carbon footprint. The insights gained from this research are invaluable for the ongoing optimization of WWTPs, contributing to enhanced environmental protection and regulatory compliance in the region. The study's findings are particularly relevant in the context of increasing urbanization and industrial activities, which lead to higher volumes of wastewater requiring treatment. By demonstrating the effectiveness of simulation tools in improving plant performance, the research offers a blueprint for other WWTPs aiming to upgrade their systems and processes. This comprehensive evaluation using advanced process simulation tools provides a robust validation of the WWTP's design and operational strategies. It highlights the plant's strengths in meeting regulatory standards and identifies areas for further optimization. The study serves as a testament to the critical role of simulation in modern wastewater management, ensuring that plants not only comply with current regulations but are also prepared to meet future challenges in wastewater treatment. This research underscores the potential of advanced technologies in driving improvements in wastewater treatment, ultimately contributing to better environmental outcomes and sustainable water resource management.
Yeni AB deşarj yönetmeliklerinin güvence altına alınması için karusel reaktörlerde havalandırmanın simülasyon tabanlı optimizasyonu
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2024
Keywords: Aerobic treatment; Aerobik arıtma; Waste water treatment; Atık su arıtma; Biological treatment; Biyolojik arıtma; Denitrification; Denitrifikasyon; Industrial waste water; Endüstriyel atık su